The shared experience of a cardiovascular research group in the context of the COVID-19 pandemic (Research, Society and Development, 2021)
Objective: to report the experience of the members of a research group on the scientific activities related to arterial hypertension in the context of the health and pandemic of Covid-19. Methodology: an experience report study about the period from March 2020 to April 2021, which was shared in the virtual environment due to the isolation and social distance imposed by the pandemic of COVID-19. Results: scientific sessions, lives, posts to publicize events, participation in an extension project and scientific production were identified in a quantitative way; while qualitative, through self-reports, a look enriched by the exchange of impressions and appreciation of everyone's learning and knowledge. Conclusion: the experience of the last 12 (twelve) months, showed how important the dynamics of continuity in the discussion, participation and contribution in the multiple activities of a research group is important.